ANALISIS KOMPARATIF PENGARUH HARGA DAN RAGAM PRODUK TERHADAP KEPUTUSAN PEMBELIAN ( STUDI KASUS PADA KOPI JANJI JIWA DAN KOPI KULO DI GRESIK ) - Septia, Mayumi; Pujianto, Agung; Maruta, IGN Anom (Universitas 17 Agustus 1945 Surabaya, 2021)
ABSTRACT Business development in modern times is growing very rapidly. One form of business that is on the rise in Indonesia is the Coffee Shop Business. Along with the rapid development of the times, lifestyles have changed. A person's current lifestyle is a lifestyle that likes to consume coffee and also a lifestyle that likes to hang out with friends or family. The method in this research is quantitative research and the type of comparative research. This research uses a research instrument in the form of a questionnaire. Sample and population are all consumers who have bought Coffee Janji Jiwa and Coffee Kulo . The purpose of this study was to determine and analyze whether there is a significant difference in price and product variety on the purchasing decision of coffee Janji Jiwa and Coffee Kulo. The analytical method used is the Independent sample t-test. The results of the study showed that there was a significant difference of 0.000 <0.05 between Price and Product Variety on the Purchase Decision of Coffee Janji Jiwa and Coffee Kulo.Keywords : Comparative Analysis, Price, Product Variety, Purchase Decision, Independent sample t-test